Digital Payments and Financial Inclusion: A Correlational Study of Microentrepreneurs from the District of Pueblo Libre, Lima, Peru 2022 - Herrera Zuasnábar, Danitza (2023)
The main objective of the research was to establish a correlation between digital payments and financial inclusion. The study also aimed to comprehend how payment systems, digital wallets, and electronic money dimensions affect financial inclusion. The research methodology used a quantitative approach with a descriptive-correlational level and a non-experimental and cross-sectional design. The study population consisted of 164 microentrepreneurs based in the district of Pueblo Libre. Data was collected through Likert-type scale surveys, and the methods of analysis were descriptive and correlational. The results showed a positive and strong correlation (0.858) between digital payments and financial inclusion. Therefore, it can be concluded that digital payments and all its dimensions contribute to financial inclusion.